The suburban townscape its origin and perspectives based on the example of a border town in Hungary (Komárom–Koppánymonostor) - Tamáska, Máté (Socio.hu Társadalomtudományi Szemle, 2016)
The paper aims to illustrate through a local study how the North American suburban townscape appears in a historical small town in Hungary. The core idea is that North American suburbanization resulted in a special suburban townscape. Instead of the traditional structure of towns and cities where the centre and periphery made up certain circles or zones, mobility axes like motorways, airports structure the suburban zone. The first chapters of the paper discuss this process and they can also be read as an independent theoretical essay. The second part of the paper shows the case study of Komárom–Koppánymonostor. Our first question is whether in this case we can speak about a suburban townscape (as a North American type). After empirical investigations the answer to the question is no. Komárom–Koppánymonostor shows a mixture of the pettybourgeois milieu typical of late socialism (and post–socialism), while the North American type of suburbanization is a new pattern of lifestyle after 2000. The second question is: what are the specific historical–social conditions that influenced the suburbanization in Komárom–Koppánymonostor? We claim that it was the Danube bank which preserved its natural environment in the phase of the rapid urbanisation of the 20th century. Finally, we claim that the suburban transformation is by no means a closed chapter seeing today’s trends. Thanks to the planned new bridge (Komárom, HU – Komárno, SK), the area of Komárom–Koppánymonostor can dissolve in future in a twin town trans–border suburban townscape. In that case, the suburban zones will get a wider dimension, in their morphology as well as in their economical potential, and they will move closer to the North American patterns. Key words: suburbanisation, border studies, divided twin towns, architecture sociology